ANALYSIS OF THE APPLICATION OF PSAK 69 ON BIOLOGICAL ASSETS AT PT AUSTINDO NUSANTARA JAYA Tbk. - Alifah Nurul Halizah Langkau1; Ambrosia Silviana Sari Saragih; Nabilah Az Zahra; Ary Noor Setyaningsih; Agma Aureole First Stecyia Payung (Transpublika Publisher, 2022)
This research aims to analyze the theory and practice of preparing financial statements carried out, especially on the recognition, measurement, and disclosure of biological assets. This research is a case study of PT Austindo Nusantara Jaya Tbk. (ANJ). The method used in this study is a qualitative research method where the data source in this study is secondary data, namely the financial statements and annual reports of PT Austindo Nusantara Jaya Tbk. (ANJ). The data analysis technique used in this study is a descriptive method of comparative qualitative approach. According to the Financial Report of PT Austindo Nusantara Jaya Tbk. (ANJ) in 2020, it shows that biological assets lie in current assets. This means that the asset has a useful life or undergoes a biological transformation in less than a year. Meanwhile, biological assets are measured by fair value minus costs for sale. The estimated fair value of biological assets will increase (decrease) if: (1) The estimated price of tbs and edamame beans is higher (lower), (2) The estimated yield is higher (lower), and (3) The estimated cost of maintenance, harvest, and transportation is lower (higher). PT Austindo Jaya Nusantara Tbk. has recognized all its biological assets with reference to the realization of production. Thus, the asset is recognized in the harvested crop.